The morphology and histology of the digestive system and associated structures of Sitobion avenae (Fabricius)(Hemiptera : Aphididae) - Laubscher, J. M.(Jacobus Martin) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.Agric.) -- Universiteit van Stellenbosch, 1985.